The Relationship Between Sleep Disorders and Stroke - Sawadogo, Wendemi; Adera, Tilahun (Handbook of the Behavior and Psychology of Disease, 2025)
Stroke is a leading cause of death and disability worldwide. It is a serious disease caused by a disruption of blood flow in the brain resulting from either blockage of blood flow to the brain (ischemic stroke) or sudden bleeding in the brain (hemorrhagic stroke). Stroke survivors experience more sleep disorders than the general population. Sleep disorders could also increase the risk of stroke even in individuals who have no history of stroke. Obstructive sleep apnea and insomnia are the most common sleep disorders associated with increased risk of stroke. Long sleep duration (≥9 h/day) and circadian rhythm changes have also been linked to an increased risk of stroke. This chapter summarizes the current evidence on the relationship between sleep disorders and stroke. © 2025 Springer Nature Switzerland AG.
Keywords: Central sleep apnea; Circadian rhythm disruption; Hypersomnia; Insomnia; Obstructive sleep apnea; Parasomnia; Sleep disorders; Sleep disturbances; Sleep movement disorders; Stroke; dept.pch